Descartes, el atomista veleidoso, o los invisibles siempre llaman dos veces - Solís Santos, Carlos (ENDOXA, 2007)
Descartes’ God put some rein to his omnipotentia absoluta (able to make a square circle), and ordained it to our particular world. Being a nice guy unwilling to cheat US, sowed our minds with the right logic and ¡deas. Burt Descartes’ key identification of matter and extensión did not work, and he was bound to accept something obscure and confuse: corpuscles without three dimensions and a size that no number can express. God omnipotentia could créate that, but in so doing he was deceiving and spoiiing the clear-and-distinct criterion.